The German Political Foundations' Work between Jerusalem, Ramallah and Tel Aviv A Kaleidoscope of Different Perspectives (Edition ZfAS, 2018)
The German political foundations are a world-wide unique phenomenon. The concept of their international work as both independent organizations and state financed institutes are naturally raising several questions. This book focus on the foundations' work in Jerusalem, Ramallah and Tel Aviv. This region holds a special position within the German foreign policy due to unique character of the German-Israeli relations and the ongoing Israel-Palestinian conflict. Israeli, Palestinian and German authors contribute to this publication by examining the history, potential influence, scope of action, chances and limits of the foundations in that region from different perspectives and with a specific focus on current developments Content · The German political foundations abroad: A collection of historical case studies · The German political foundations from an anthropological, political science and law perspectives · The German political foundations between Jerusalem, Ramallah and Tel Aviv: Reflections from within · The German political foundations between Jerusalem, Ramallah and Tel Aviv: Local Partners and Outsiders Perspectives Target Groups · Political scientists · History scientists · Humanities researchers The Editors Anna Abelmann is Research Associate of the Ruhr University of Bochum. Katharina Konarek is Research Associate of the Haifa Center for German and European Studies at University of Haifa.